2018
DOI: 10.7150/ijbs.25996
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 Signaling in Retinal Ganglion Cells under Oxidative Stress in Ocular Neurodegenerative Diseases

Abstract: Retinal ganglion cells (RGCs) are one of the important cell types affected in many ocular neurodegenerative diseases. Oxidative stress is considered to be involved in retinal RGCs death in ocular neurodegenerative diseases. More and more attention has been focused on studying the agents that may have neuroprotective effects. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a key nuclear transcription factor for the systemic antioxidant defense system. This review elucidates the underlying mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 89 publications
4
41
0
1
Order By: Relevance
“…Then, transcription of antioxidant enzymes and phase II detoxification enzymes occurs, including heme oxygenase-1 (HO-1), NAD(P)H: quinone oxidoreductase 1 (NQO1) [17]. Also, g-glutamyl cysteine ligase catalytic subunit (GCLC), glutathione peroxidase [13], glutathione-S-transferase (GST), catalase, superoxide dismutase, and thioredoxin uridine 5'-diphospho-glucuronosyltransferase) (UDP)-glucuronosyltransferase occurs [18][19][20][21]. However, Nrf2 may be dissociated from the cytoplasmic Nrf2-keap1-cul3 complex by p62, which is a marker of cell autophagy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Then, transcription of antioxidant enzymes and phase II detoxification enzymes occurs, including heme oxygenase-1 (HO-1), NAD(P)H: quinone oxidoreductase 1 (NQO1) [17]. Also, g-glutamyl cysteine ligase catalytic subunit (GCLC), glutathione peroxidase [13], glutathione-S-transferase (GST), catalase, superoxide dismutase, and thioredoxin uridine 5'-diphospho-glucuronosyltransferase) (UDP)-glucuronosyltransferase occurs [18][19][20][21]. However, Nrf2 may be dissociated from the cytoplasmic Nrf2-keap1-cul3 complex by p62, which is a marker of cell autophagy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid 2‐related factor 2 (Nrf2) is an important transcription factor that regulates cellular antioxidant activity and has been shown to protect organs in several animal models . Nrf2–mediated antioxidant gene expression can reduce the macrophage M1 phenotype and ROS production; therefore, activating the Nrf2 pathway may inhibit the progression of inflammation and may be a potential therapeutic strategy for many disorders such as cardiovascular diseases, neurodegenerative diseases and multiple sclerosis . Moreover, Nrf2 has been reported to be an important regulator in protecting against TBI–induced secondary brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…The current study confirmed that an APAP and ROX co-treatment increased the MDA level and depressed GPX and SOD activities ( Figure 5), suggesting the impairment of hepatic redox homeostasis, accumulation of ROS and formation of lipid peroxidation. Co-treatment significantly increased the mRNA expression of Nrf2 (Figure 6), which is significant because the activated Nrf2 is a transcription factor that modulates endogenous antioxidant enzymes [18,19]. APAP and ROX stimulate Nrf2 activation, which binds to the antioxidant response element and further activates the transcription of gene-encoding for antioxidants and detoxification, including haem oxygenase-1 (HO-1), NADPH, quinone oxidoreductase-1 (NQO-1) and glutathione-synthesising enzymes glutamatecysteine ligase catalytic subunit (GCLC).…”
Section: Discussionmentioning
confidence: 96%